Justiça desportiva: proposta de classificação jurisdicional - Raguza, Carlos Henrique (2018)
One of the subjects with few studies, but that represents one of the foundations of the Law, is the jurisdiction. Its historical origin is intrinsically related to the evolution of society, and the practical purpose of discussing this interesting institute is to understand the growing search for alterative solutions to conflicts. It couldn’t be ignored, in a discourse on jurisdiction, the concept of the State, from its formation, to the most recent three Powers theory, and the system of checks and balances inserted in the Federal Constitution. On the other hand, the Judiciary is a clearer and more evident manifestation of the jurisdiction practical application, and its concept and characteristics, the extension and, finally, the limits of jurisdiction are extracted. Once composed of a solid scientific substrate, we present the didactic classification currently accepted and well accepted by most of the doctrine, closing the first stage of this paper. The static scenario, from this point onwards, is the subject of provocations, in which obstacles as exceptions to the inafasability of jurisdiction, notably by the presentation of alternative methods of conflict resolution, ilustrates the current needs of a dynamic, complex and constantly changing society. Increasingly, there is the presence of private nature entities in conflict resolution, including through international cooperation among countries. Arbitration is the most classic example of an alternative method of conflict resolution, whose performance and participation of private entities is a result of the strengthening of the expression of will in clauses and contracts more prestigiously designed to the autonomy of the parties. The Sport Court, in its turn, although autonomous and independent, maintains certain influence of the State due to its traces of public, social law. And article 217, especially §§ 1 and 2, could have extended these characteristics if the text had clearly restricted the matter to be known by the Judiciary, in order to confer greater permanence to the decisions rendered by the Courts of Sports Justice. Although a long way to go, the study that we propose come from premises seen and recognized by the various branches of law, in order to establish a reasoning that leads to a proposal of repositioning the jurisdiction and, consequently, the Sports Court. Comparative analysis, similarity of some procedural aspects, applicable principles and decisions in the field of Arbitration and Sports Justice undoubtedly depict a fertile substratum for legal constructions, a challenge that we intend to follow and overcome